2017
DOI: 10.1016/j.pcd.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of implementation of a preconception counselling resource for women with diabetes: A population based study

Abstract: Publisher rights © 2016 Elsevier Ltd. This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/bync-nd/4.0/ which permits distribution and reproduction for non-commercial purposes, provided the author and source are cited. General rightsCopyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 23 publications
1
27
1
Order By: Relevance
“…To summarise each of the five studies show a mixed range of improvement in glycaemic control. However, only one study showed very little improvement [15]. Most of the studies showed at least some improvement.…”
Section: Glycaemic Controlmentioning
confidence: 91%
See 4 more Smart Citations
“…To summarise each of the five studies show a mixed range of improvement in glycaemic control. However, only one study showed very little improvement [15]. Most of the studies showed at least some improvement.…”
Section: Glycaemic Controlmentioning
confidence: 91%
“…Holmes, Hamill, Alderdice, et al [15] showed a very little improvement rate (less than 5% difference in results of mean HbA1c between the intervention and control group) in glycaemic control. The overall difference in glycaemic control between the two groups was not as significant (a mean HbA1c of 7.4% in the intervention group vs 7.3% in the group with no intervention).…”
Section: Glycaemic Controlmentioning
confidence: 95%
See 3 more Smart Citations